Inequalities in obesity in Portugal: regional and gender differences - Alves, L (2017)
Background: Obesity levels vary considerably according to geographical region and socio-economic status. We evaluated the prevalence of obesity by education and occupational position across seven Portuguese regions. Relative and absolute inequalities in obesity were also assessed. Methods: Data was drawn from the Portuguese Health Survey 2005/6 (26 674 adults, 46.6% women). Education was categorized as ≤4, 5–11 and ≥12 complete years of education. Occupational position was grouped as upper white collar, lower white collar and blue collar. The Relative Index of Inequality (RII) and the Slope Index of Inequality (SII) were used to quantify relative and absolute inequalities in obesity, respectively. Results In women, prevalence of obesity ranged between 10.0% (Algarve) and 20.3% (Azores); in men, it ranged between 13.3% (Algarve) and 16.4% (Lisbon). In women, the educational RII (95% confidence interval) ranged between 2.4 (1.1 to 5.1) in the Centre and 6.6 (3.0 to 14.2) in Alentejo, and the SII (95% CI) between 9.7 (−1.3 to 20.7) and 33.0 (26.0 to 40.0), respectively. In men, the RII ranged between 0.8 (0.4 to 1.5) in Madeira and 1.9 (1.0 to 4.5) in the Centre, and the SII between −8.3 (−19.0 to 2.5) and 9.5 (−0.1 to 19.1), respectively. Occupational RIIs were similar to those for education, although somewhat lower. Conclusion In Portugal, large educational and occupational inequalities in obesity are observed, but they vary considerably by region and are larger among women than men.